My family community - Kalman, Bobbie (New York : Crabtree Pub., 2010)
How is a family a community? This book shows young readers that, like a community, a family has members who perform roles. Parents teach and care for their children and go to work to earn money for the family; children have rules to follow and household jobs to perform. Cooperation and communication between family members keeps the family community strong.
Print version record.
Keywords: Families -- Juvenile literature; Families; Families; Juvenile works